Telemedicine as a mesure to prevent falls in older people in their homes: literature review - Reina Miranda, David (Enfermería Cuidándote, 2024)
Introduction: This bibliographical review is based on the premises that 33% of people over 65 years old fall each year and that 10% of them suffer serious injuries and the increase in the use of telemedicine due to the COVID-19 pandemic. For this reason, the effectiveness of telemedicine as a fall prevention tool in people over 65 years old residing at home was investigated. Methodology: The methodology has been divided into two: one of a more general nature (narrative search) and another with the research question itself (more structured, exhaustive and methodological search). The following databases were used: PubMed, Cochrane Library, CUIDEN Plus, CINAHL, SCOPUS, and SciELO. Mainly using the MeSH descriptors: “Telemedicine”, “Accidental falls”, “Aged” and “Treatment outcome”. Results: After which 10 studies were finally selected to form part of the bibliographic review. These studies present a good methodological quality and a high level of evidence (level I). The analysis of the results revealed significant changes mainly in the rate of falls, as well as in other physical skills such as the level of activity, strength, balance, gait speed, among others. Conclusions: In this bibliographical review, the effectiveness of telemedicine programs for the prevention of falls in the elderly is demonstrated in a significant way. The studies found especially measure motor results, for this reason it is proposed a future research to include a more holistic analysis.